ANÁLISIS DE LA ACTITUD DE INNOVACIÓN TECNOLÓGICA EN EL PERÚ: EL CASO DE LOS MEDIOS DE COMUNICACIÓN ELECTRÓNICA - Hidalgo Sánchez, Augusto (2008)
Technological innovation in Peru happens randomly. Historically, the actors for the economic and social development of the country seem not to be aware of the importance of technology adoption. They behave concentrated on the economic or political profits, and carelessly regarding its impact on development. This is confirmed by this short narration about the incorporation of electronic media technology in Peru.